(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazione SOMMARIO: 1. Introduzione – 2. Pluralismo della "responsabilità" – 3. Significati – 4. Williams e i materiali universali della responsabilità. – 5. "La responsabilità" e "le responsabilità". Una proposta di ridefinizione: "responsabilità-soggezione" e "responsabilità per ruolo" – 6. Responsabilità-soggezione – 7. Responsabilità per ruolo – 8. Significati di "ruolo" – 9. Il meccanismo "accettazione–riconoscimento" - 10. "Responsabilità per ruolo" e responsabilità giuridica – 11. La Chiesa “hierarchica communio” – 12. Ruoli e responsabilità tra diritto dello Stato… – 13. ...e diritto della Chiesa – 14. La responsabilità canonica tra diritto e morale – 15. Gli abusi: la giustizia che non ripara - 16. Giustizia riparativa: verso un nuovo diritto della responsabilità. AbstractThe scandal of sexual abuse of children by the Catholic clergy has focused attention on the theme of responsibility and its functions in our society. This paper explores two concepts of responsibility, distinguishing between a retrospective responsibility and a prospective responsibility. The first one corresponds to a punitive legal model adopted in our legal system. The second one is congruent to a restorative model of justice, which is emerging as a new paradigm within criminal law. This paper considers the particular conditions and forms of responsibility in canon law, in comparison with the secular legal model. The conclusion is that the responsibility in Church law is a retrospective one, focused on punishment of the offender rather than the needs of the victim.